Pancreas collagen digestion during islet of Langerhans isolation—a prospective study. (28th September 2020) - Meier, Raphael P. H.; Meyer, Jeremy; Muller, Yannick D.; Szot, Gregory L.; Bédat, Benoît; Andres, Axel; Massé, Nathalie; Lablanche, Sandrine; Puppa, Giacomo; Bosco, Domenico; Berney, Thierry
Abstract: The success of pancreas islet isolation largely depends on donor characteristics, including extracellular matrix composition of which collagen is the main element. We hypothesized that isolation yields are proportional to collagen digestion percentage, and aimed to determine a threshold that predicts isolation success. The amount of pancreas collagen (I‐V) was determined using colorimetry prior to and after the digestion process in 52 human islet isolations. Collagen I‐V and VI were also assessed histologically. We identified a collagen digestion threshold of ≥ 60% as an independent factor beyond which an islet preparation has a ninefold increased odds of yielding ≥ 250 000 islet equivalents (IEQ) ( P  = 0.009) and a sixfold increased odds of being transplanted ( P  = 0.015). Preparations with ≥ 60% collagen digestion ( n  = 35) yielded 283 017 ± 164 214 IEQ versus 180 142 ± 85 397 in the < 60% collagen digestion group ( n  = 17) ( P  = 0.016); respectively 62.9% versus 29.4% of those were transplanted ( P  = 0.024). Common donor characteristics, initial collagen content, enzyme blend, and digestion times were not associated with collagen digestion percentage variations. Donor age positively correlated with the amount of collagen VI ( P  = 0.013). There was no difference in islet graft survival between high and low digestion groups. We determined that a 60% pancreas collagen digestion is the threshold beyond which an islet isolation is likely to be successful and transplanted.